2010
DOI: 10.1016/j.rse.2010.05.029
|View full text |Cite
|
Sign up to set email alerts
|

The temporal dimension of differenced Normalized Burn Ratio (dNBR) fire/burn severity studies: The case of the large 2007 Peloponnese wildfires in Greece

Abstract: 9The temporal dimension of differenced Normalized Burn Ratio (dNBR) fire/burn severity 10 studies was studied for the case of the large 2007 Peloponnese wildfires in Greece. Fire 11 severity is defined as the degree of environmental change as measured immediately post-fire, 12 whereas burn severity combines the direct fire impact and ecosystems responses. Geo were retrieved using time series similarity of a pre-fire year. The analysis incorporated the 18 optimality statistic, which evaluates index performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 77 publications
(109 reference statements)
4
101
0
11
Order By: Relevance
“…Such studies are particularly important as NASA continues to develop new sensors with multiple spectral bands in the thermal infrared such as the planned Hyperspectral Infrared (HyspIRI) HyspIRI sensor (http://hyspiri.jpl.nasa.gov/). Due to the characteristic temporal dynamics of the post-fire environment, the utility of adding T s in the fire severity assessment will heavily depend on the post-fire acquisition timing [14,59,75]. Veraverbeke et al [75] showed that, although the post-fire T s is long lasting, the magnitude of change rapidly alters as time elapses after the fire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies are particularly important as NASA continues to develop new sensors with multiple spectral bands in the thermal infrared such as the planned Hyperspectral Infrared (HyspIRI) HyspIRI sensor (http://hyspiri.jpl.nasa.gov/). Due to the characteristic temporal dynamics of the post-fire environment, the utility of adding T s in the fire severity assessment will heavily depend on the post-fire acquisition timing [14,59,75]. Veraverbeke et al [75] showed that, although the post-fire T s is long lasting, the magnitude of change rapidly alters as time elapses after the fire.…”
Section: Resultsmentioning
confidence: 99%
“…This impact can be described as: (i) the amount of damage [3][4][5]; (ii) the physical, chemical and biological changes [6][7][8][9][10]; or (iii) the degree of alteration [11,12] that fire causes to an ecosystem. In this context, the terms fire severity and burn severity are often used interchangeably [2], however, Lentile et al [13] and Veraverbeke et al [14], suggest a clear distinction between both terms by considering the fire disturbance continuum [15], which addresses three different temporal fire effects phases: before, during and after the fire. In this framework fire severity quantifies the short-term fire effects in the immediate post-fire environment while burn severity quantifies both the short-and long-term impact as it includes response processes.…”
Section: Introductionmentioning
confidence: 99%
“…The S-G method is suitable for this proposal, since other smoothing methods cannot capture a sudden change of the temporal values, for example Fourier series or least squares fitting to sinusoidal functions [73][74][75]. The choice of the window width in the S-G filter is essential to provide smoothing without loss of resolution.…”
Section: Noise Eliminationmentioning
confidence: 99%
“…For the Kalamata meteorological station (37°4' N, 22°1' E) the average 150 annual temperature is 17.8 °C and the mean annual precipitation equals 780 mm (Hellenic 151 National Meteorological Service, www.hnms.gr, accessed 20 December 2010). The fires 152 consumed more than 175 000 ha, which merely consisted of shrub land and pine forest 153 (Veraverbeke et al, 2010a). Black pine (Pinus nigra) is the dominant conifer species.…”
Section: Study Area 139mentioning
confidence: 99%